Celebrating the First Decade of Democracy in South Africa (1994-2004 ): An Inter-religious Perspective - Dolamo, RTH (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
In this article, apartheid is singled out as a scourge that has afflicted South Africans for four-and-half decades. Against this backdrop, the struggles of the people of South Africa, particularly of the churches and the religious communities as a whole, are portrayed and analysed. With the attainment of freedom and democracy in 1994, the ANC led government enacted pieces of legislation, the aim of which was to deepen and broaden democracy, thereby transforming the society beyond recognition of how it was before 1994. Celebrating the first ten years of freedom and democracy, the people of South Africa were taking stock of what has been achieved and not achieved and bracing themselves for the challenges that are facing them into the second decade of democracy.